Comparison of functional disability measures and clinical variables in rheumatoid arthritis - (:unkn) unknown (My University, 2003)
In this study we investigated the relationship between the clinical and the functional disability parameters in rheumatoid arthritis (RA) patients and compared the related factors for functional disability questionnaires. Demographic data of RA patients were recorded. Clinical parameters including; pain by VAS, tenderness by Ritchie articular index (RAI), swelling of joints, morning stiffness and radiological changes were determined. Health assessment questionnaire (HAQ), arthritis impact measurement scale (AIMS) and Duruöz's Hand Index (DHI) were used to assess functional disability. The correlation between the clinical, radiological parameters and functional disability indices were investigated. The relationship between the clinical parameters of the patients and disability indices were also determined, according to the disease duration and seropositivity. Fifty patients (40 women) with a mean age of 47.7±11.1 years completed the study. The mean scores of HAQ and DHI were best correlated with each other and all subgroups of AIMS, except for the depression and exiety. Radiologic scores, gender and rheumatoid factor were not correlated with disability. The scores of VAS-pain, RAI and joint swelling were the best-related variables for the disability scores. No association was found between the mean disease duration of patients and scores of functional status. Disability was slightly but not significantly higher in sero (+) than in sero (-) patients. The functional disability scores in patients with long and short disease duration were not significantly different. The clinical variables of the RA patients correlated well with the physical domains of functional disability questionnaires. Pain and tenderness appear to be the most related factors for disability. Functional disability seems to be important both in patients with long and short disease duration, regardless to the seropositivity.
Keywords: Arthritis Impact Measurement Scale (AIMS); Duruöz's Hand Index (DHI); Functional Disability; Health Assessment Questionnaire (HAQ); Rheumatoid arthritis